Patients’ and Healthcare Personnel’s Experiences of Health Coaching with Online Self-Management in the Renewing Health Project - Inger Lindberg (International Journal of Telemedicine and Applications, 2017)
Background. Telehealth applications have shown positive effects for people with chronic conditions and their awareness of health. Objective. To describe patients’ and healthcare personnel’s experiences of using health coaching with online self-management in primary health care. Method. A pragmatic randomised controlled trial was conducted. Patients in the intervention group measured and reported medical parameters such as blood pressure, blood glucose, prothrombin complex (PK) values, and 2-channel ECG. Data were collected through a questionnaire, individual interviews with patients, and focus group discussions with healthcare personnel. The questionnaire was analysed using statistics; texts from interviews and focus groups were analysed using content analysis. Findings. Patients were satisfied and believed that the intervention had enhanced their care and increased accessibility without causing concerns about privacy. Although being positive, patients commented the lack of support and feedback from healthcare personnel. Healthcare personnel regarded the intervention valuable for the patients’ abilities to perform self-management healthcare tasks but preferred that patients did so without them supporting the patients. Conclusion. Patients expressed satisfaction and acceptance regarding the use of the application. It seems that healthcare personnel are convinced about the benefits for patients and the potential for the intervention but are not convinced about its benefits for healthcare organisations.